Políticas públicas e trabalho precário : a retórica da “autonomia empreendedora” e a permanência do desemprego - Oliveira, Vanessa Dias de (2017)
In the face of the disastrous picture of unemployment, an ideology is spreading in today's social policies: that of "autonomous" work as a viable means of insertion to guarantee employability. This comes just after the unfolding of the structural crisis in Brazil in the 1980s and 1990s, when the productive restructuring and all its flexible package merged the depletion of the industrialization pattern with the Neoliberal project, dismantling the fragile status of social policies that, Had been implemented after the 1988 Constitution. The financialisation of capital by imposing administrative reform of the state, cuts in social spending, trade liberalization, privatization, appropriation of the public fund and, above all, the deregulation of labor relations, seeks to capture the most inexpensive and unprotected labor in the most strategic territories. The barbarization of the "social issue" is manifested by chronic unemployment, outsourcing, intensification of informal relations, worsening job quality and increased poverty, especially in urban spaces. In order to face it, a public employment system was implemented in 1990, consisting of income transfer policies (salary bonus, unemployment insurance), workforce intermediation, stimulation of professional qualification in addition to credit granting through Employment and Income Generation Program (PROGER). In view of this, the thesis aimed to unveil the role of public policies of labor and income "employment", through the largest program to combat unemployment in Latin America PROGER (Program for the Generation of Employment and Urban Income) in the retreat or favoring the growth of relative overpopulation. The marxian/marxist theoretical foundation, combined with research and information in the Worker Support Fund, Ipea, Dieese, IBGE, from interviews with municipal managers and workers excluded from PROGER-Urban in Aracaju / SE, allow us to affirm that the policy of granting credit operates on two lines and does not reach the most vulnerable subjects, being innocuous in the minimum fight against unemployment. The management principles of Proger-Urban depend on the bureaucracy of financial institutions (Banco do Brasil, Caixa Econômica Federal, Banco do Nordeste, etc.), and the working conditions of the brazilian labor market, whose precariousness and informality are traits essential, are related to predatory financial accumulation, preventing the generation of work and income along the lines proposed by the program. In the context of Aracaju, the "non-employable", who survive in the margins of labor market policies, enter into the uncertainty of informal occupations, linked to the "third sector" through "voluntary and solidarity" work, in the case of the Recycling Agents Cooperative (CARE). The other workers who remain unemployed seek the intermediation of labor to compete for jobs in the labor market; end up being channeled to the training of technical qualification courses offered by SINE / FAT at the Municipal Labor Foundation, or remain unemployed, increasing the functional contingent to capital. The real subsumption, camouflaged by counter-propensity, takes on such a reified character that it obscures the function of the State and capital in the control of labor, allowing the extraction of absolute and relative surplus value in new formats, favored by the increase of "Non-employable".